The Influence of Perceived Education Quality on Self-Efficacy Using the Structural Equation Modeling (SEM) Approach with AMOS - Anjarwati, Rina; Malihah, Elly (JURUSAN MANAJEMEN PENDIDIKAN FAKULTAS ILMU PENDIDIKAN UNIVERSITAS NEGERI GORONTALO, 2024)
The purpose of this study is to examine the impact of Perceived Education Quality on Academic Self-Efficacy, specifically in the context of students majoring in hospitality and tourism. This research employs a quantitative approach, with data analysis conducted using the Structural Equation Modeling (SEM) method, operated through AMOS 24 software, to evaluate the relationship between exogenous and endogenous variables. A questionnaire was distributed to 200 respondents via a Google Form link, targeting hospitality and tourism students in Bandung as the sample. This study involves two variables: Perceived Education Quality as the exogenous variable and Academic Self-Efficacy as the endogenous variable. The findings indicate that Perceived Education Quality has a positive and significant effect on Academic Self-Efficacy. Educational institutions are encouraged to focus on enhancing Perceived Education Quality by improving teaching methods, curriculum design, learning resources, and facilities to foster students' self-efficacy and improve academic outcomes. For future research, it is recommended to explore additional variables such as institutional reputation, student engagement, and technological integration. Expanding the research context to different educational settings or cultural environments would also provide more comprehensive insights. Moreover, investigating mediating and moderating variables, such as motivation and academic stress, could further deepen the understanding of these relationships.